Pattern recognition receptor polymorphisms in early periodontitis. Issue 6 (19th December 2018) - Leite, Fábio R. M.; Enevold, Christian; Bendtzen, Klaus; Baelum, Vibeke; López, Rodrigo
Abstract: Background: Even though bacteria trigger inflammation, most of the tissue destruction in periodontitis is due to the host inflammatory response. In addition to immunological events that drive development of early periodontitis, numerous environmental factors like genetics and smoking play a role. We investigated whether the carriage of selected single nucleotide polymorphisms (SNP) of toll‐like receptors (TLR), NOD‐like receptors (NLR) and RIG‐I‐like receptors (RLR) was associated with the diagnosis of early periodontitis in a case‐control study. Methods: Adolescents with positive (n = 87) and negative (n = 73) diagnosis for periodontitis had blood samples taken. All participants were genotyped for 42 SNP in the genes encoding TLR1‐10, NOD1‐2, DDX58, and IFIH1 using multiplex assays. Associations between SNP and periodontitis diagnosis were tested. Results: TLR1‐rs5743611 showed protective effect for periodontitis (CC versus GG and GC, P  = 0.01, odds ratio [OR] 0.10, 95% confidence interval [CI] 0.01‒0.78). Carriage of the TLR4‐rs7873784 was associated with higher odds for periodontitis (GG versus CC and GC, P  = 0.05, OR 2.30, 95% CI 1.00‒5.63; GG versus GC, P  = 0.05, OR 2.46, 95% CI 1.01‒5.99). In male participants, reduced susceptibility to periodontitis was observed in carriers of TLR7‐rs3853839 (CC versus GG and CG, P  = 0.02, OR 0.30, 95% CI 0.11‒0.85) and TLR8‐rs3764879 (CC versus GG and CG, P  = 0.02, OR 0.31, 95% CI 0.12‒0.82). Associations were maintained after adjustments for sex, smoking habits, and mother´s education. Conclusion: This study demonstrated an association between TLR1‐rs5743611, TLR4‐rs7873784, TLR7‐rs3853839, and TLR8‐rs3764879 and susceptibility to periodontitis in adolescents.